Unbalanced, Idle, Canonical and Particular: Polysemous Adjectives in English Dictionaries - Jonathan Stammers (Lexis: Journal in English Lexicology)
This study seeks to compare how various English dictionaries distinguish multiple meanings, focusing on a particular class of words identifiable in dictionary classification, namely, polysemous adjectives. The polysemy displayed by adjectives tends to be of a heavily context-dependent type. A great deal of the literature concerning polysemy has little bearing upon adjectives. Adjectives are also a varied word-class, thus posing a range of challenges to the lexicographer. This study looks at six recently published British monolingual dictionaries of English, both for native speakers and advanced learners. A random sample (based on Collins English Dictionary) of adjectives with many senses is selected, and their respective dictionary entries compared and evaluated, following analysis of corpus data. The random sample chosen prove a quite heterogeneous set, with some appearing to be not true adjectives; others to be not truly polysemous; some having a clear hierarchy of senses; others much less clear. Differences between senses are often highly subtle and contextually determined, forming a semantic cline, or continuum of senses, which dictionaries often divide quite differently. Detailed results are shown here for four of the adjectives, unbalanced, idle, canonical and particular, and other results discussed in brief.